2005
DOI: 10.1016/j.fertnstert.2005.01.134
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ conceptualization of their frozen embryos complicates the disposition decision

Abstract: Objective-To ascertain what couples think about their embryos and how they approach making a decision about disposition in light of the fact that the disposition of unused frozen embryos has significant implications for medical research and embryo donation.Design-Ethnographic qualitative interview study. Setting-Academic research environment.Patient(s)-Fifty-eight couples who had conceived using a donor oocyte and had at least one frozen embryo in storage.Main Outcome Measure(s)-Tape-recorded interviews with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 6 publications
0
47
1
5
Order By: Relevance
“…Contrary to other studies of the disposition decision that found a sense of resolution amongst their respondents [7], we found a lingering sense of discomfort and uncertainty amongst many of our respondents. This finding is in contrast to the altruistic motives cited in other studies by those who donated pre-embryos to research, and were less ambivalent about their decision than those who decided to destroy [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to other studies of the disposition decision that found a sense of resolution amongst their respondents [7], we found a lingering sense of discomfort and uncertainty amongst many of our respondents. This finding is in contrast to the altruistic motives cited in other studies by those who donated pre-embryos to research, and were less ambivalent about their decision than those who decided to destroy [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Although the decision to donate to research can have firm motivations – commonly described by donors as better than the thawing of embryos and as an opportunity to help others or to improve health and IVF treatments [3] – some reports have shown that as many as 88 % of couples who had originally chosen to donate their embryos to research changed their minds [7]. Yet there has been scant research on how patients who have stored frozen embryos actually think about them or what are their motivations and deliberations concerning the disposition decision [8].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy was that dimensions of the experience included descriptions of the interplay of religious beliefs and altruism. Although the indecisiveness in terms of embryo disposition described by some of the women may be attributed to the unknown outcome of their pregnancies, another qualitative analysis of donor oocyte recipient women and their husbands found 72% of them were undecided despite having cryopreserved embryos for 1 to 11 years duration ( Nachtigall, Becker, Friese, Butler, & MacDougall, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with previous studies, reasons for not donating were lack of confidence in medical science [14,16]; the incomprehensibility [15] and inconvenience of the content of the research; and the embryo being recognized as a virtual sibling [9,12,14,18,24],]. As in Kato & Sleeboom-Faulkner’s study, we also found that the thought of dissecting an embryo or transforming it into another form was considered disrespectful by those opposed to donation [24].…”
Section: Discussionmentioning
confidence: 86%